A biotype of hare barley (Hordeum leporinum) resistant to paraquat and diquat - Tucker, E.S.; Powles, S.B. (Cambridge University Press, 1991)
A biotype of the annual grass weed hare barley infesting an alfalfa field with a 24-yr history of the use of the bipyridylium herbicides paraquat and diquat, was investigated for resistance to these herbicides. Rates of up to 800 g ai ha–1 of each herbicide caused no mortality in the hare barley plants from this field. The same species, collected from an adjacent pasture field with no history of bipyridylium herbicide application, exhibited LD50's of 57 and 160 g ai ha–1 for paraquat and diquat, respectively. Tiller numbers and dry matter production in the biotype from the alfalfa field were not affected by the normal rate recommended for both herbicides. These results clearly show that hare barley from the alfalfa field is resistant to paraquat and diquat. Both biotypes were equally sensitive to fluazifop, glyphosate, and sethoxydim.